What are Sub-National Island Jurisdictions? - Steffen Eriksen; Bert Scholtens; Stephanie Werleman (Cogent Social Sciences, 2025)
There is no consensus about the definition and classification of Sub-National Island Jurisdictions (SNIJs). This may conflate academic and policy analysis and misguide policies to advance development. We review existing definitions and classifications of SNIJs and systematically analyze the criteria used in different studies. Our study finds several inconsistencies in existing lists of entities labelled as SNIJs. This shows it may be helpful to arrive at common ground as to what might constitute an SNIJ. We suggest to define an SNIJ as a non-sovereign populated island territory that possesses some degree of autonomy in a partnership with a parent state. SNIJs have their own identity and culture, which are distinct from the parent state. They often are former colonies and may freely move towards independence. This definition can be used as a starting point for further analysis and of SNIJs that can help study them and design policies that address their challenges.